Fuzzy Ce-I(ec,eo) and Fuzzy Completely Ce-I(rc,eo) Functions via Fuzzy e-Open Sets - V. Seenivasan; K. Kamala (The Scientific World Journal)
We introduced the notions of fuzzy Ce-I(ec,eo) functions and fuzzy completely Ce-I(rc,eo) functions via fuzzy e-open sets. Some properties and several characterization of these types of functions are investigated.